Fungi And Plant Diseases - V.K GUPTA; Y.S. Paul (New Delhi Kalyani, 2012)
The revised book "Fungi and plant diseases"is a volume consisting of seven chapters dealing on different aspects of Fungi and diseaes caused by them
Plant Diseases caused fungi stramenopila protoctista
Keywords: Plant Diseases caused fungi, stramenopila, protoctista